Assessment of the Language Program used in the Municipality of Medellín to teach English as a Foreign Language through the analysis if its linguistic and socio-culturak impacts (2018)
ABSTRACT: A foreign language “is used to denote a language acquired in a milieu where it is normally not in use” (Cook, 2011, p. 140). Colombia has acknowledged a significant interest in the learning of English as a foreign language. In Colombia, students in public high schools learn English as a foreign language through the National Bilingual Program. During the learning process, students are exposed to the target language through different strategies to acquire the language and fulfill the program expectations. Hitherto, national and international exams have been the only instruments used to assess the language proficiency level and the students’ learning process. This program still requires information about the linguistic and sociocultural implications of this type of education on students who have been in the learning program for several years. Thus, a descriptive study was done by carrying out a survey and an interview with 1068 students of 10th and 11th grade in Medellin, detecting statistical difference between genders. Furthermore, exploration and assessment of institutional documents and historical reports of a standard exam were completed in order to have a wider view of the foreign language acquisition process in a Spanish-speaking context. In addition, a historical report of the standard exam SABER 11 was executed before performing some in-class observations in EFL classrooms of public institutions. Therefore, the observation of the linguistic product in public schools is relevant to understand the use of the languages, the evolution English is having around the world and the growth of EFL in Spanish speaking contexts. This analysis aims to measure the effects this education has had on the students’ lives academically and culturally. This inquiry took into consideration the information provided by the students as the direct participants impacted for this type of education, official documents, standard exams and classes recordings. In this manner, it shows a broader view of the learning process, the population and the linguistic conditions and impacts this type of learning can have in the city and the country. This study contributes to the enrichment of public policy about the teaching and learning of Foreign Languages in Spanish speaking contexts.